Improving Writing in English Using the Inquiry Method at Seven Grade Students SMP Islam Rengasdengklok - Muhammad Abdul Malik; Yanti Rusmiati (Universitas Muhammadiyah Enrekang, 2022)
Abstract: IMPROVING WRITING ARTICLE IN ENGLISH USING THE INQUIRI METHODE AT SEVEN GRADE STUDENTS SMP ISLAM RENGASDENGKLOK, the purpose of this research is to improve students' ability to use articles in English. Talking about grammar, a special problem that students often face is students' ignorance in applying English articles. A condition where students easily make mistakes in applying English articles into a sentence. The main reason is because the teaching of articles is limited and often neglected. In fact, articles are important in terms of communication for Indonesian students. For junior high school students at MTs Rengasdengklok tend to have difficulty in obtaining articles because their mother tongue does not have the same language. So that the correct use of articles is a challenge for students at MTs Rengasdengklok. Then in this study the author uses the action research method which consists of 4 stages, namely planning, implementing actions, observing, reflecting, with a comparison of increasing values ​​from cycle 1 (45%) and cycle 2 (92%) using the inquiry method with an increase in value of 47 % of total success 100%. Keywords: Teaching, Articles, Junior High School.